A case of combination of Eales disease and Arnold Chiari syndrome - V.S. Ponomarchuk; N.I. Naritsyna; N.V. Konovalova; T.M. Serebrina; V.B. Reshetniak (Ukrainian Society of Ophthalmologists, 2016)
Purpose. A description of a rare combination of Arnold - Kiari syndrome and Eales Disease is given. Material and Methods. We followed up a 24 y.o. patient with Eales Disease combined with Arnold - Kiari syndrome. Results. According to clinical and functional examination data, a patient was diagnosed Ealse disease. Taking into account changes in the optic disc which are not typical for that disease, a patient was performed MRT of the head which revealed the presence of Arnold - Kiari syndrome. Conclusion. The present clinical case is evidence of combination of Arnold - Kiari syndrome and Eales Disease, thus, practical ophthalmologist should have that in mind and examine patients carefully.